Meibomian Lipid Films and the Impact of Temperature - Butovich, Igor A. (Association for Research in Vision and Ophthalmology, Inc., 2010)
PURPOSE. There is evidence that, in cold conditions, the temperature of human eyelids and of the ocular surface drops well below normal physiological levels. This may have a detrimental impact on the stability and functionality of the human tear film and the tear film lipid layer. The goal of this project was to quantitatively examine the possible impact of temperature on the latter. METHODS. Meibum samples were collected by using a soft-squeezing technique and were studied in a Langmuir trough. The obtained surface pressure and area isotherms were analyzed to determine the biophysical parameters of thin meibomian lipid film (MLF): the lift-off area, collapse pressure, two-dimensional elasticity, and hysteresis and their dependence on temperature. RESULTS. MLF was found to be highly susceptible to changes in temperature. At temperatures below the physiological level, the MLF became stiff and shrank considerably. The shrinkage left a large portion of the air–water interface uncovered with lipid molecules. The effect was shown to be reversible. On reheating, the lipids melted and respread to restore the original film. There was a fundamental difference observed between three-dimensional melting of dry meibum in bulk and the two-dimensional melting in MLF at the air–water interface. Bulk meibum melted in a narrower temperature range and showed a much higher cooperativity of melting. CONCLUSIONS. Temperature critically influences MLF. Low temperature leads to stiffening of the film, which loses its ability to form continuous layers at the air–water interface. These effects were shown be of a cooperative nature, manifesting in relatively narrow concentration and temperature ranges.